Non-destructive studies of the internal structure of concrete of different grades - Dyussambayev, D.S.; Aitkulov, M.T.; Madiyanova, A.N.; Kasymov, A.B.; Bugybay, Zh.T.; Kiselev, K.S.; Akhanov, A.M. (Recent Contributions to Physics, 2022)
Concrete is one of the most common building materials that is used in many areas of human activity, from the construction of residential buildings to industrial buildings and more. In the nuclear power industry, concrete is used not only as a structural material, but also as a material for biological protection. Usually concrete mix consists of cement, coarse and fine aggregates, water and various additives. Based on the field of application of concrete, the correct ratio of its components is selected. This paper presents the results of a study of the effect of the composition of concrete on its internal structure. The studies were carried out by the non-destructive method of neutron radiography and tomography at the facility, which is located on one of the horizontal channels of the WWR-K reactor. As a result of the studies carried out by the non-destructive method of neutron radiography and tomography, concrete samples of three different types of brands were studied. The distribution of pores and cracks in each sample is shown. The attenuation coefficients of neutron radiation for the studied concrete grades are given. The rate of water migration in concrete of different grades is estimated. The applicability of the neutron radiography and tomography installation for this type of investigation of the internal structure of concrete was demonstrated.